Analysis of the functional compatibility of SIV capsid sequences in the context of the FIV gag precursor - Ovejero, César Antonio (2017)
The formation of immature lentiviral particles is dependent on the multimerization of the Gag polyprotein at the plasma membrane of the infected cells. One key player in the virus assembly process is the capsid (CA) domain of Gag, which establishes the protein-protein interactions that give rise to the hexagonal lattice of Gag molecules in the immature virion. To gain a better understanding of the functional equivalence between the CA proteins of simian and feline immunodeficiency viruses (SIV and FIV, respectively), we generated a series of chimeric FIV Gag proteins in which the CA-coding region was partially or totally replaced by its SIV counterpart. All the FIV Gag chimeras were found to be assembly-defective; however, all of them are able to interact with wild-type SIV Gag and be recruited into extracellular virus-like particles, regardless of the SIV CA sequences present in the chimeric FIV Gag. The results presented here markedly contrast with our previous findings showing that chimeric SIVs carrying FIV CA-derived sequences are assembly-competent. Overall, our data support the notion that although the SIV and FIV CA proteins share 51% amino acid sequence similarity and exhibit a similar organization, i.e., an N-terminal domain joined by a flexible linker to a C-terminal domain, their functional exchange between these different lentiviruses is strictly dependent on the context of the recipient Gag precursor.